PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MATA PELAJARAN IPS EKONOMI MATERI POKOK PASAR KELAS VIII-A SMP NEGERI 1 ASEMBAGUS - Miftahus Surur (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
Based on the interview result that is done by researcher with Economic teacher of VIII-A Class at State Junior High School 1 Asembagus, researcher finds that“learning model that applied in Economic school subject in market material was conventional learning model,which are lecture, discussion, and assignment. The interview was related to the implementation of conventional learning model, he said that conventional learning model was appropriated to apply inclass who has big students and make teacher easily to dominate class.So, it’s needed to update the implementation of learning model to increase the learning quality. The objective of this study was to describe the implementation of Snowball Throwing learning model in increase student’s learning activity and learning result on Economic subject with market material on Class VIII-A State Junior High School 1 Asembagus. This study was classroom action research. This study will be held in two cycles, and each cycle consists of four phases, which are planning, action, observation, and reflection. And the data collecting technique which used in this study were interview, documentation, observation, and test. The implementation of Snowball Throwing learning model can increase student’s learning activity from percentage degree 68% on the first cycle to the 86% on the second cycle. In the other hand, the implementation of Snowball Throwing learning model can increase student’s learning outcomes from classical mastery degree 69% on the first cycle to the 96% on the second cycle. It can be concluded that the implementation of Snowball Throwing learning model can increase student’s learning activity and learning outcomes on Economic subject with market material on Class VIII-A State Junior High School 1 Asembagus.